Safety voice and safety listening during aviation accidents: Cockpit voice recordings reveal that speaking-up to power is not enough. (July 2021) - Noort, Mark C.; Reader, Tom W.; Gillespie, Alex
Highlights: Safety voice – the act of speaking-up about safety – is assumed to prevent harm. Yet, evidence from real accidents remains scant, limiting intervention design and training. In contrast to prevailing thought, flight crew spoke-up across real aviation accidents. This was explained by poor safety listening and high power distance. CRM training has improved safety voice, but only for lower power distance countries. Abstract: Safety voice is theorised as an important factor for mitigating accidents, but behavioural research during actual hazards has been scant. Research indicates power distance and poor listening to safety concerns (safety listening) suppresses safety voice. Yet, despite fruitful hypotheses and training programs, data is based on imagined and simulated scenarios and it remains unclear to what extent speaking-up poses a genuine problem for safety management, how negative responses shape the behaviour, or how this can be explained by power distance. Moreover, this means it remains unclear how the concept of safety voice is relevant for understanding accidents. To address this, 172 Cockpit Voice Recorder transcripts of historic aviation accidents were identified, integrated into a novel dataset (n = 14, 128 conversational turns), coded in terms of safety voice and safety listening and triangulated with Hofstede's power distance. Results revealed that flight crew spoke-up in all but two accidents, provided the first direct evidence that power distance and safety listening explain variation in safety voice during accidents, and indicated partial effectiveness of CRM training programs because safety voice and safety listening changed over the course of history, but only for low power distance environments. Thus, findings imply that accidents cannot be assumed to emerge from a lack of safety voice, or that the behaviour is sufficient for avoiding harm, and indicate a need for improving interventions across environments. Findings underscore that the literature should be grounded in real accidents and make safety voice more effective through improving 'safety listening'.